Comment on “Moral Thought: Evaluation on the Moral Education and Virtue Cultivation of Traditional Chinese Music” - Gang Du (Trans/Form/Ação)
Commented article: WANG, H. Moral thought: evaluation on the moral education and virtue cultivation of traditional Chinese music. Trans/Form/Ação, v. 47, n. 5, p. e02400167, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14871.